Strategi sektor perbankan menghadapi ancaman non performing loan pada masa pandemic COVID-19 - Tyahya Whisnu Hendratni; DW Soemarsono; Hindradjid Harsono (LPMP Imperium, 2022)
This study aims to determine the effect of inflation, interest rates, and ROE on NPL in Commercial Banks, how the banking sector strategy faces the threat of NPL during the Covid-19 Pandemic, and how the implementation of government policies and their effects on NPL. ROE, Interest Rates, and Inflation on the dependent variable, name. The data used in this study is secondary data, which is panel data sourced from financial reports published on the official website www.idx.co.id. Inflation occurs due to excess demand for several products or services and encourages an increase in overall product prices; inflation will undoubtedly be accompanied by rising interest rates for savings and loans. As a result, the value of non-performing loans owned by banks tends to increase. The higher inflation will encourage an increase in the tendency of the importance of NPL owned by a bank. The higher inflation will promote growth in the direction of the value of NPL. Inflation has a significant positive effect on NPL owned by a bank. The results of this study indicate that the rise and fall or ROE can affect the increase or decrease in NPL.